2023
DOI: 10.1039/d2cb00205a
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterisation of G-quadruplex DNA-forming sequences in the Pseudomonas aeruginosa genome

Abstract: A number of Gram-negative bacteria such as Pseudomonas aeruginosa are becoming resistant to front-line antibiotics. Consequently, there is a pressing need to find alternative bio-molecular targets for the development of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…S5†). 72,73 Together, these results suggest that the modification has negligible impact on the structure and stability of a Telo GQ. Similarly, EGFR ONs 3–5 and control unmodified ONs 6 and 7 were annealed in 10 mM Tris·HCl buffer (pH 7.4), and the formation of GQ structures with an increase in K + ion concentration was monitored by CD spectroscopy.…”
Section: Resultsmentioning
confidence: 80%
“…S5†). 72,73 Together, these results suggest that the modification has negligible impact on the structure and stability of a Telo GQ. Similarly, EGFR ONs 3–5 and control unmodified ONs 6 and 7 were annealed in 10 mM Tris·HCl buffer (pH 7.4), and the formation of GQ structures with an increase in K + ion concentration was monitored by CD spectroscopy.…”
Section: Resultsmentioning
confidence: 80%
“…All tested molecules were able to stabilize G4s, with TMPyP4 showing the strongest efficacy among the small panel of tested compounds. Moreover, Ni-salphen has shown a moderate selectivity for ftsB and mexC G4s with respect to the murE G4, while PDS has been observed to stabilize the ftsB G4 with a two-step mechanism, suggesting that the ligand might shift among multiple binding sites or that it could bind to different topologies of the G4, even though further studies are needed to validate these hypotheses …”
Section: Role Of G4s In Bacteria and Their Modulation By Small Moleculesmentioning
confidence: 99%
“…19,20 While, recent studies have revealed the presence of quadruplex forming sequences in Gram-negative bacteria suggesting a possible avenue to develop G4 targeting antibiotics to tackle antimicrobial resistance. 21 Additionally, the presence of G4 structures in viral genomes, including RNA viruses and SARS-CoV-2 makes, further highlights its potential as a therapeutic target. 22,23 The excellent photophysical and electrochemical properties of transition metal polypyridyl complexes make them attractive candidates for DNA targeting, imaging, and phototherapeutic applications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Consequently, anticancer drugs that target G4 are actively being pursued with a number in clinical trials approved, , while there is also interest in developing diagnostic molecular probes to recognize these structures . The diversity of oncogene targets is further evidenced by their ability to form coupled ternary structures. , While, recent studies have revealed the presence of quadruplex forming sequences in Gram-negative bacteria suggesting a possible avenue to develop G4 targeting antibiotics to tackle antimicrobial resistance . Additionally, the presence of G4 structures in viral genomes, including RNA viruses and SARS-CoV-2 makes, further highlights its potential as a therapeutic target. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation